MicroRNA expression profiles in human cancer cells after ionizing radiation - Niemoeller, Olivier M (BioMed Central, 2011)
INTRODUCTION: MicroRNAs are regulators of central cellular processes and are implicated in the pathogenesis and prognosis of human cancers. MicroRNAs also modulate responses to anti-cancer therapy. In the context of radiation oncology microRNAs were found to modulate cell death and proliferation after irradiation. However, changes in microRNA expression profiles in response to irradiation have not been comprehensively analyzed so far. The present study's intend is to present a broad screen of changes in microRNA expression following irradiation of different malignant cell lines. MATERIALS AND METHODS: 1100 microRNAs (Sanger miRBase release version 14.0) were analyzed in six malignant cell lines following irradiation with clinically relevant doses of 2.0 Gy. MicroRNA levels 6 hours after irradiation were compared to microRNA levels in non-irradiated cells using the "Geniom Biochip MPEA homo sapiens". RESULTS: Hierarchical clustering analysis revealed a pattern, which significantly (p = 0.014) discerned irradiated from non-irradiated cells. The expression levels of a number of microRNAs known to be involved in the regulation of cellular processes like apoptosis, proliferation, invasion, local immune response and radioresistance (e. g. miR-1285, miR-24-1, miR-151-5p, let-7i) displayed 2 - 3-fold changes after irradiation. Moreover, several microRNAs previously not known to be radiation-responsive were discovered. CONCLUSION: Ionizing radiation induced significant changes in microRNA expression profiles in 3 glioma and 3 squamous cell carcinoma cell lines. The functional relevance of these changes is not addressed but should by analyzed by future work especially focusing on clinically relevant endpoints like radiation induced cell death, proliferation, migration and metastasis.